Revolusi Digital dalam Meningkatkan Daya Saing UMKM di Desa Wonosunyo, Pasuruan Jawa Timur - Adhar Putra Setiawan; Mar’uf Sya’ban; Marista Oktaviani (Pusat Riset dan Inovasi Nasional, 2025)
Digital marketing has become an essential instrument in expanding business reach and improving the competitiveness of small and medium enterprises (SMEs) in the current digital era. However, many SME entrepreneurs, particularly in rural areas, still rely on conventional marketing approaches that limit their ability to adapt to technological advancements. This study was conducted in Wonosunyo Village with the aim of enhancing the digital literacy and understanding of digital marketing among local SME entrepreneurs. The community service program was designed to provide training, mentoring, and practical guidance related to the use of digital technology in business development. The activities included the introduction of digital marketing concepts, market research techniques, branding strategies, and product packaging improvements. Furthermore, participants were guided in utilizing various social media platforms and e-commerce channels as promotional and sales tools to reach broader markets beyond their local communities. The mentoring process emphasized a hands-on approach, allowing participants to directly practice creating digital content, managing online stores, and analyzing consumer behavior through available digital tools. The results of the program showed that participants gained new insights and practical skills in applying digital marketing strategies, which encouraged a shift from traditional to more innovative business practices. It is expected that the improvement in digital literacy will contribute to increased sales, expanded customer bases, and greater adaptability of SMEs in facing the challenges of digital transformation. This program highlights the importance of integrating technology into the business activities of SMEs, particularly those in rural settings, as a strategy to enhance efficiency, effectiveness, and competitiveness. The findings also demonstrate that community service initiatives can play a strategic role in empowering local entrepreneurs and ensuring that SMEs remain sustainable in the face of rapid technological and market changes.